2013
DOI: 10.2147/ppa.s44646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reducing dosing frequency on adherence to oral therapies: a literature review and meta-analysis

Abstract: ObjectivesTo assess the impact of reduced frequency of oral therapies from multiple-dosing schedules to a once-daily (OD) dosing schedule on adherence, compliance, persistence, and associated economic impact.MethodsA meta-analysis was performed based on relevant articles identified from a comprehensive literature review using MEDLINE® and Embase®. The review included studies assessing adherence with OD, twice-daily (BID), thrice-daily (TID), and four-times daily (QID) dosing schedules and costs associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 63 publications
4
59
0
Order By: Relevance
“…Few studies have assessed patient adherence to medication for the chronic treatment of nonmalignant pain 2123. Here a patient SRQ method was used to directly determine patient-reported adherence to PPI treatment when coprescribed with NSAIDs to prevent upper gastrointestinal ulcers in patients with OA, RA, or AS.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed patient adherence to medication for the chronic treatment of nonmalignant pain 2123. Here a patient SRQ method was used to directly determine patient-reported adherence to PPI treatment when coprescribed with NSAIDs to prevent upper gastrointestinal ulcers in patients with OA, RA, or AS.…”
Section: Discussionmentioning
confidence: 99%
“…In A-HeFT, adherence was high at 84.6% (22). Medications that require three times a day administration are expected to have lower adherence in comparison to a once a day medication (23). In this VHA study, over 95% of the H-ISDN prescribed was as a generic formulation.…”
Section: Discussionmentioning
confidence: 99%
“…34 In FREEDOM-EV, oral treprostinil was dosed TID; 21 although this could help reduce the intensity of adverse effects to allow increasing the dose to a therapeutic level, 34 TID dosing could introduce adherence issues compared with a drug with less frequent dosing. 35,36 The primary limitation of this study is that whereas the index drugs are indicated solely for specified patients with PAH (not other forms of PH) there is no unique ICD-9-CM or ICD-10-CM code for PAH. 37 Both coding systems have a diagnostic code for primary pulmonary hypertension, which corresponds to idiopathic PAH in the current PAH classification, [38][39][40] but they have no codes that differentiate the other PAH subgroups from non-PAH forms of PH.…”
Section: Clinical Guidelines Current During the Study Period Gave A Cmentioning
confidence: 99%